A PLS-SEM Based Approach: Analyzing Generation Z Purchase Intention Through Facebook’s Big Data - Vikas Kumar; Preeti; Shaiku Shahida Saheb; Sunil Kumari; Kanishka Pathak; Jai Kishan Chandel; Neeraj Varshney; Ankit Kumar (Big Data Mining and Analytics)
The objective of this paper is to provide a better rendition of Generation Z purchase intentions of retail products through Facebook. The study gyrated around the favorable attitude formation of Generation Z translating into intentions to purchase retail products through Facebook. The role of antecedents of attitude, namely enjoyment, credibility, and peer communication was also explored. The main purpose was to analyze the F-commerce pervasiveness (retail purchases through Facebook) among Generation Z in India and how could it be materialized effectively. A conceptual façade was proposed after trotting out germane and urbane literature. The study focused exclusively on Generation Z population. The data were statistically analyzed using partial least squares structural equation modelling. The study found the proposed conceptual model had a high prediction power of Generation Z intentions to purchase retail products through Facebook verifying the materialization of F-commerce. Enjoyment, credibility, and peer communication were proved to be good predictors of attitude (R2=0.589) and furthermore attitude was found to be a stellar antecedent to purchase intentions (R2=0.540).